CANINE MONOCYTIC EHRLICHIOSIS: PATHOGENESIS, DIAGNOSIS, TREATMENT AND CLINICAL OUTCOMES - S.P. Abhijith; A. Abdul Kalam; H.J. Apoorva (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Canine ehrlichiosis is a globally significant, tick-borne disease of dogs, primarily transmitted by Rhipicephalus sanguineus, the brown dog tick. The etiological agents, belonging to the genus Ehrlichia (notably Ehrlichia canis, E. chaffeensis, and E. ewingii), are obligate intracellular Gram-negative bacteria that parasitize monocytes, granulocytes, or platelets, leading to a complex spectrum of clinical manifestations. The disease is classically divided into acute, subclinical, and chronic phases, each associated with varying degrees of hematological abnormalities, including thrombocytopenia, anaemia, and leukocyte dysfunction, accompanied by nonspecific systemic signs such as fever, lethargy, weight loss, lymphadenopathy, and bleeding tendencies. In chronic infections, pancytopenia and bone marrow suppression often carry a poor prognosis. Diagnosis relies on a combination of hematological evaluation, serology, and advanced molecular techniques such as PCR, which remain the gold standard for species-specific identification. Therapeutic approaches commonly involve tetracycline derivatives, especially doxycycline, often combined with supportive management to address secondary complications. Preventive strategies emphasize tick control and emerging vaccine research. Despite significant advances in understanding host-pathogen interactions, immune evasion mechanisms, and diagnostic modalities, challenges persist in early detection, resistance management, and regional epidemiological surveillance. This review consolidates current knowledge on canine ehrlichiosis with emphasis on epidemiology, pathogenesis, clinical features, diagnosis, treatment, prevention, and future perspectives.